2020
DOI: 10.1186/s12890-020-1136-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of social factors to readmissions within 30 days after hospitalization for COPD exacerbation

Abstract: Background To investigate whether, in patients hospitalized for COPD, the addition of social factors improves the predictive ability for the risk of overall 30-day readmissions, early readmissions (within 7 days after discharge), and late readmissions (8–30 days after discharge). Methods Patients (aged ≥40 years) hospitalized for COPD were identified in the Medicare Current Beneficiary Survey from 2006 through 2012. With the use of 1000 bootstrap resampling from the original cohort (training-set), two predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
1
12
2
Order By: Relevance
“…Regarding an overall rate of 30-days readmission, our finding (21(18.01%)) was almost similar with studies conducted in Chicago [37], Ohio [38], Spain [26], and USA [39] which revealed an overall 30-days readmission rate of 18.5%, 18.1%, 17.98%, and 19.4% respectively. However, it's inconsistent with studies conducted by Buyantseva et al [40], and Meservey et al [41] that reported a higher 30-days readmission rate of 39%, and 23% respectively.…”
Section: Plos Onesupporting
confidence: 88%
“…Regarding an overall rate of 30-days readmission, our finding (21(18.01%)) was almost similar with studies conducted in Chicago [37], Ohio [38], Spain [26], and USA [39] which revealed an overall 30-days readmission rate of 18.5%, 18.1%, 17.98%, and 19.4% respectively. However, it's inconsistent with studies conducted by Buyantseva et al [40], and Meservey et al [41] that reported a higher 30-days readmission rate of 39%, and 23% respectively.…”
Section: Plos Onesupporting
confidence: 88%
“…Females have an increased risk of hospitalization for COPD compared with males [relative risk (RR) = 1.5 (1.2–2.1) to 3.6 (1.4–9)] 143 . Female representation among patients hospitalized for COPD exacerbation is increasing over time 147 and females are at higher risk of readmission 148 …”
Section: Is Gender Important In Copd?mentioning
confidence: 99%
“…This indicated that XGBoost model was better than logistic model in predicting the risk of readmission in patients with AECOPD within one year. Currently, the prediction of the risk of readmission in patients with AECOPD was focused on 30 days and 90 days after treatment and discharge [ 10 12 , 40 ], but 30 days or 90 days could not actually represent the disease procession. The readmission of AECOPD patients within one year indicated the long-term prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there was no international universal prediction model for predicting the readmission of AECOPD patients within one year after discharge. Prediction models of readmission in patients with AECOPD were established based on the data of USA or UK people and some of them were focused on predicting the risk of readmission of AECOPD patients within 30 days based on social factors or LACE index (length of stay, acuity of admission, co-morbidities, and emergency department visits within the last 6 months) [ 10 , 11 ]. Additionally, the prediction models for readmission of AECOPD patients within 90 days were also established based on PEARL (previous admissions, eMRCD score, Age, Right-sided heart failure and Left-sided heart failure) or COPD-2-HOME score (CAT score, hyperinflation, obstruction, prior admission, eosinophilia) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%